COUNTERACTION OF CORRUPTION IN MODERN RUSSIA: INTERACTION BETWEEN GOVERNMENT AND CIVIL SOCIETY - Elena Galkina (Гуманитарные и юридические исследования)
This paper examines the current mechanisms for participation of civil society in combating corruption in modern Russia. The various research approaches to the concepts of combating corruption in the modern political science and legal discourse. Urgent consideration is the author of new concepts in the involvement of civil society institutions in the state important projects, including the prevention of corruption.